Moisture Transport for Reaction Enhancement in Fabrics. (3rd March 2013) - Gibson, Phillip; Schreuder-Gibson, Heidi; Yip, Pearl; Denker, Brendan; Benaddi, Hamid; Wang, Sa; Bromberg, Lev; Hatton, T. Alan
Abstract : The role of water in protective fabrics is critical to comfort and material performance. Excessive perspiration in clothing causes discomfort, and bound water can adversely affect the ability of carbon to adsorb chemicals. Yet the presence of water can also improve the moisture vapor transport of protective polymer films, and is essential for the hydrolytic destruction of nerve agents. Reported here are the findings of wicking and drying experiments conducted on various hydrophilic and hydrophobic cover fabrics that demonstrate the influence of wetting on permeation through fabrics. The influence of water content on reactive polymers capable of degrading nerve agent simulant is also discussed, and the importance of a novel "delivery system" for water to the reactive components through the use of a wicking fabric is introduced.